2009
DOI: 10.1002/pmic.200800244
|View full text |Cite
|
Sign up to set email alerts
|

Exploring membrane and cytoplasm proteomic responses of Alkalimonas amylolytica N10 to different external pHs with combination strategy of de novo peptide sequencing

Abstract: Identification of differentially proteomic responses to external pHs would pave an access for understanding of survival mechanisms of bacteria living at extreme pH environment. We cultured Alkalimonas amylolytica N10 (N10), a novel alkaliphilic bacterium found in Lake Chahannor, in media with three different pHs and extracted the correspondent membrane and cytoplasm proteins for proteomic analysis through 2-DE. The differential 2-DE spots corresponding to the altered pHs were delivered to MALDI TOF/TOF MS for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…While extracting the membrane fraction from the rest of the cell constituents added a very modest increase in protein hits, adding a membrane solubilisation step significantly increased the detection of membrane proteins (Figures 1A, B). The breadth of solubilisation methods available in the literature (Schuck et al, 2003;Eshaghi et al, 2005;Williams et al, 2007;Wang et al, 2009;Zaparty et al, 2009;Burton and Martin, 2012;Altinisik Kaya et al, 2018) leaves a plethora of options available, but it is well noted that there is no common optimal method. Given our knowledge of membrane proteins, we opted for the use of detergents.…”
Section: Proteomics Protocol Optimisation For Detection Of C Thermaru...mentioning
confidence: 99%
See 1 more Smart Citation
“…While extracting the membrane fraction from the rest of the cell constituents added a very modest increase in protein hits, adding a membrane solubilisation step significantly increased the detection of membrane proteins (Figures 1A, B). The breadth of solubilisation methods available in the literature (Schuck et al, 2003;Eshaghi et al, 2005;Williams et al, 2007;Wang et al, 2009;Zaparty et al, 2009;Burton and Martin, 2012;Altinisik Kaya et al, 2018) leaves a plethora of options available, but it is well noted that there is no common optimal method. Given our knowledge of membrane proteins, we opted for the use of detergents.…”
Section: Proteomics Protocol Optimisation For Detection Of C Thermaru...mentioning
confidence: 99%
“…For alkaliphiles, two studies have been reported. One investigates membrane solubilisation with urea in Alkalihalobacillus marmarensis (Altinisik Kaya et al, 2018), while the other focuses on a few other well-known yet ultimately ineffective detergents for Alkalimonas amylolytica (Wang et al, 2009). None of these studies rely on a comparative approach that assesses the contribution of each step to the protocol.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, proteomic analysis revealed that the expression level of membrane proteins participating in the ion transport in the haloalkaliphilic bacterium Alkalimonas amylolytica strain N10, which grows at NaCl concentrations up to 7% and with an optimum pH of 10 to 10.5 [15] , varies according to changes in pH and salt concentration [16] . This indicated the ion transporters are important for adaptation to high pH and salt in this haloalkaliphile.…”
mentioning
confidence: 99%